The Choice Of Maize (Zea Mays L.) Storage Facility Among Farmers In The Sissala East District In Northern Ghana: What Are The Determinants? - Adams, A. A.; Akrofi, M.N.A.; Sarpong, D.B. (Journal of Stored Products Research, 2025)
Maize (Zea mays L.) is crucial to food security in Ghana but is characterized by high postharvest losses (PHLs) resulting from the use of traditional storage structures. As poverty and food insecurity are rampant in northern Ghana, improved storage of maize, a staple food, is vital for boosting household food security. This study analyzed factors influencing farmers’ choice for improved maize storage facilities in the Sissala East District, a vital supplier of maize to neighboring districts in the Upper West Region and Ghana at large, where maize farming is the main source of income for farmers. Twenty-one communities and 132 maize farmers were sur veyed. A multi-stage sampling technique was employed: purposive selection of the communities followed by a random selection of maize farmers from each community. Traditional storage facilities are still prevalent, while most farmers use small facilities with a maximum stocking capacity of 50 bags of 100 kg of maize. Many farmers used Corchorus olitorius (jute) sacks, while only five communities had a common warehouse. Regression results show that smallholder farmers with access to extension services were more likely to use improved storage fa cilities like warehouses, silos, and improved barns and storerooms. Farm characteristics such as farm size and productivity were strong determinants of the choice of an improved storage facility. Also, socio-economic factors such as age of the farmer, number of years in farming (experience), and access to non-farm income sources were associated with the use of improved maize storage facilities. PHLs, as a share of the average output of maize harvested per annum, were higher for farmers using traditional storage than improved storage. Extension services on improved methods of maize storage to boost adoption, improve maize productivity, and increase food availability are recommended. Community warehouses should be constructed. Sensitization on the extent of PHLs should be emphasized.
Research Article
Keywords: Stored maize; Postharvest losses; Ghana; Improved storage; Food security; Binary logit